Determination of the Strategic Position of the Iran Pentathlon Association - Mahdi Goudarzi (Research in Sport Management and Marketing)
Purpose: The purpose of this study was to determine the strategic Position of Iran Pentathlon Association. Methods: The relevant literatures were reviewed and also the survey and PEST SCAN (Cronbach Alpha = 0.88) questionnaires and SWOT analysis were used for data collection. 21 current managers and experts together with in Pentathlon Association were selected to complete the questionnaires. By Delphi method, meetings and several strategic analyzing steps, 11 strengths, 10 weaknesses, 8 opportunities and 13 threats were recognized and ranked based on Friedman test. Results: The results of this research show that the total scores of the matrix of internal factors of the Pentathlon Association is 2.13, which is weak in terms of internal factors, and in the evaluation matrix of external factors, the total weighted scores of external factors show the number 2.07, which in terms of external factors has is a threat.Conclusion: The strategic position of the Iranian Pentathlon Association was determined using the evaluation matrix of internal and external factors in the WT position, therefore, the total weighted points of the internal and external factors evaluation shows the defensive position, which strategies should be formulated and selected based on this situation.